The Role of Women and Peace Building: A Case Study of Inong Bale in Aceh - Milena Rahmanova (Budapest International Research and Critics University, 2022)
In the spiral of conflict and violence, women tend to be the most vulnerable parties to become victims of conflict. Women are one of the parties most affected by the war, this is because women are often victims of violence and injustice due to gender discrimination and pre-existing social strata. Inong Balee is one of the wings of the GAM struggle which is considered by the central government as part of the separatist movement in the Aceh conflict era. Inong Balee has an important role in GAM as well as to complement GAM's struggle during the Aceh conflict. In the case of Inong Bale, the application of the post-conflict bottom-up women's movement model could be the most appropriate approach in the transition process. With the cooperation of all relevant parties.The Role of Women and Peace Building: A Case Study of Inong Bale in Aceh